2013
DOI: 10.1002/cnm.2610
|View full text |Cite
|
Sign up to set email alerts
|

Studying the influence of hydrogel injections into the infarcted left ventricle using the element‐free Galerkin method

Abstract: Myocardial infarction is an increasing health problem worldwide. Because of an under-supply of blood, the cardiomyocytes in the affected region permanently lose their ability to contract. This in turn gradually weakens the overall heart function. A new therapeutic approach based on the injection of a gel into the infarcted area aims to support the healing and to inhibit adverse remodelling that can lead to heart failure. A computational model is the basis for obtaining a better understanding of the heart mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In this study, the mechanical model proposed by Usyk et al [23] and reformulated in terms of the invariants of the Green strain tensor, E, by Legner et al [26] was considered for our human biventricular models. The model describes the myocardium as a nonlinear, orthotropic, and nearly incompressible hyperelastic material using the strain energy function given by:…”
Section: Constitutive Model For Elastic Myocardiummentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the mechanical model proposed by Usyk et al [23] and reformulated in terms of the invariants of the Green strain tensor, E, by Legner et al [26] was considered for our human biventricular models. The model describes the myocardium as a nonlinear, orthotropic, and nearly incompressible hyperelastic material using the strain energy function given by:…”
Section: Constitutive Model For Elastic Myocardiummentioning
confidence: 99%
“…In terms of the Dirichlet boundary conditions, the ventricles were fixed at the base as shown in Figure 2A to prevent the heart from undergoing rigid body motion in the vertical direction and to allow for the connections between the base and the major blood vessels. The heart experiences a degree of twist during muscular contraction; to allow for this torsional behavior, but still restrict the deformation to a physiologically normal level, another Dirichlet boundary condition was weakly imposed through the application of an elastic line force with spring constant k = 0.1 kN/mm acting in the tangential direction around the epicardial base, as seen in Figure 2B [26,27]. The elastic line forces effectively prevent rigid body motion in the short axis direction, but do not obstruct ventricular wall thickening.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…Material injections that result in increased stiffness to the infarct region have also been shown to lower stresses in the infarcted and healthy regions of the heart in subject-specific ovine LV FE models [ 67 ] (Fig. 4 ) and for idealised ellipsoid LV models [ 96 ]. Improvements to cardiac function seen in the subject-specific ovine FE model such as wall thickening and increased ejection fraction [ 67 ] are consistent with in vitro and in vivo experiments [ 97 ].…”
Section: Modelling Of Materials Injection Therapies For MImentioning
confidence: 99%
“…[10] Computer simulations and finite element analyses have demonstrated that biomaterial stiffness, degradation, and injection location can significantly alter efficacy of therapy. [9, 13,14] Matsumura and colleagues recently were the first to demonstrate efficacy of a synthetic biomaterial, utilizing a relatively stiff (275kPA) material. [15] Synthetic materials have numerous advantages, including the ability to tune material degradation and stiffness properties.…”
Section: Introductionmentioning
confidence: 99%